2018
DOI: 10.1002/aelm.201800224
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Current‐Induced Magnetization Switching Utilizing Interlayer Exchange Coupling

Abstract: Electrical current-induced deterministic magnetization switching in a magnetic multilayer structure without external magnetic field is realized by utilizing interlayer exchange coupling. Two ferromagnetic Co layers, with in-plane and out-of-plane anisotropy respectively, are separated by a spacer Ta layer, which plays a dual role of inducing antiferromagnetic interlayer coupling, and contributing to the current-induced effective magnetic field through the spin Hall effect. The current-induced magnetization swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 27 publications
3
63
0
2
Order By: Relevance
“…To realize this aim, we design the device in heavy metal (HM)/FM/AFM/FM structure, where the bottom and top FM layers are perpendicular magnetic anisotropy (PMA) and in-plane anisotropy, respectively. 29 In this work, we report the tunability of VMS and EB by SOT in at positive (2200 Oe) and negative (-2200 Oe) field, respectively], which is much larger than that reported in conventional field-cooling AFM/FM system. [9][10][11][12] As the positive and negative Ip have nearly the same effect on switching out-of-plane interfacial spins under Hz, 28 we measured the device using a single pulse 40 mA under Hz = -2 kOe [ Fig.…”
mentioning
confidence: 70%
“…To realize this aim, we design the device in heavy metal (HM)/FM/AFM/FM structure, where the bottom and top FM layers are perpendicular magnetic anisotropy (PMA) and in-plane anisotropy, respectively. 29 In this work, we report the tunability of VMS and EB by SOT in at positive (2200 Oe) and negative (-2200 Oe) field, respectively], which is much larger than that reported in conventional field-cooling AFM/FM system. [9][10][11][12] As the positive and negative Ip have nearly the same effect on switching out-of-plane interfacial spins under Hz, 28 we measured the device using a single pulse 40 mA under Hz = -2 kOe [ Fig.…”
mentioning
confidence: 70%
“…[20] The interlayer exchange coupling due to Ruderman-Kittel-Kasuya-Yosida interaction between two FM layers has been also used to enable field-free magnetization switching. [18] In this study, the symmetry of two states of perpendicular magnetization was broken due to the exchange coupling to a layer with in-plane magnetization. Thus, the deterministic switching could be achieved and, moreover, could be tuned by switching the in-plane magnetization direction.…”
Section: Field-free Deterministic Magnetization Switching By Sotsmentioning
confidence: 93%
“…In this study, the symmetry of two states of perpendicular magnetization was broken due to the exchange coupling to a layer with in‐plane magnetization. Thus, the deterministic switching could be achieved and, moreover, could be tuned by switching the in‐plane magnetization direction …”
Section: Manipulation Of Magnetic Materials By Spin–orbit Torquesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] In the conventional SOT structure of a heavy metal (HM)/ferromagnet (FM) bilayer, in which spin current is generated by spin Hall effect (SHE) in HM and/or interfacial spin-orbit coupling (ISOC) effect at the HM/FM interface, the direction of spin polarization is found to be orthogonal to both charge and spin current directions. [1,3,[10][11][12][13] Among the extensive reports to achieve SOTinduced switching without an external magnetic field, [14][15][16][17][18][19][20] our previous study showed that an out of plane (or z-) component of spin polarization is generated in a magnetic trilayer of FM/ Ti/CoFeB structure, [21] where the bottom FM (top CoFeB) has www.advelectronicmat.de using perpendicular (B z ) or in-plane (B x , B y ) magnetic fields to measure hysteresis loops of the samples. Since the spin polarization is aligned in the film plane, an external magnetic field is required for SOT-induced switching of perpendicular magnetization.…”
Section: Introductionmentioning
confidence: 99%